2017
DOI: 10.3233/bir-17131
|View full text |Cite
|
Sign up to set email alerts
|

The autodigestion hypothesis: Proteolytic receptor cleavage in rheological and cardiovascular cell dysfunction1

Abstract: Transformation of circulating leukocytes from a dormant into an activated state with changing rheological properties leads to a major shift of their behavior in the microcirculation. Low levels of pseudopod formation or expression of adhesion molecules facilitate relatively free passage through microvessels while activated leukocytes with pseudopods and enhanced levels of adhesion membrane proteins become trapped in microvessels, attach to the endothelium and migrate into the tissue. The transformation of leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…However, it is clear that hydrolytic enzymes released by leukocytes, such as collagenase, elastase and matrix metalloproteinase-9, degrade important structural components of the endothelial glycocalyx, basement membrane, and ECM, thereby contributing to leukocyte-dependent microvascular barrier dysfunction in postischemic tissues (Altshuler, Kistler & Schmid-Schonbein, 2016; Carden & Korthuis, 1996; Granger & Korthuis, 1995; Kalogeris et al, 2012, 2016; Schmid-Schonbein, 2016). …”
Section: Mediators Generated By the Proteolytic Activity Of Emigratedmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is clear that hydrolytic enzymes released by leukocytes, such as collagenase, elastase and matrix metalloproteinase-9, degrade important structural components of the endothelial glycocalyx, basement membrane, and ECM, thereby contributing to leukocyte-dependent microvascular barrier dysfunction in postischemic tissues (Altshuler, Kistler & Schmid-Schonbein, 2016; Carden & Korthuis, 1996; Granger & Korthuis, 1995; Kalogeris et al, 2012, 2016; Schmid-Schonbein, 2016). …”
Section: Mediators Generated By the Proteolytic Activity Of Emigratedmentioning
confidence: 99%
“…For example, it is not clear what role protease-dependent receptor cleavage (Schmid-Schonbein, 2016; Mazor & Schmid-Schonbein, 2015) might play in postischemic EDD dysfunction. Moreover, interesting recent work has demonstrated that pentraxin 3, a soluble pattern recognition receptor that plays an important role in innate immune responses, induces EDD dysfunction via a P-selectin/MMP-dependent pathway that may feed into our hypothesized mechanism (Carrizzo, Lenzi, Procaccini, Damato, Biagioni, Ambrosio et al, 2015).…”
Section: Summary and Future Directionsmentioning
confidence: 99%